Stark broadening of isolated ion lines by plasmas - Breger, Peter (Department of Physics, 2024)
'!'his study focuses on the development and the evaluation of a practical Stark broadening calculation of isolated ion line widths by Hey. In particular, emission profiles produced by optically thin plasma sources are considered. Despite the development of the fully quantum mechanical theory in the impact regime by Baranger, the semi-empirical and semi-classical approximations by Griem have been widely used in the practical prediction of widths of isolated lines. Hhereas these approximations achieved fair success for singlyionised emitters, discrepancies have been widely reported in the application to the more highly-ionised species. In order to make use of the advantages offered by the classical path approximation, a new derivation of the effective Gaunt factor appearing in the excitation crosssections has been carried out. In particular, this function is derived with proper allowance for curvature of the electron (perturber) orbit. Careful examination of the restrictions on a classical path approximation is seen to lead to a Gaunt factor based in spirit on the approach used by Griem, but achieving a continuity as a function of energy for all abovethreshold energies, as well as a reduction to the correct limiting behaviour at high energies (Bethe approximation). The extension of the Gaunt factor into the below-threshold energy regime for inclusion of elastic contributions to the broadening is thus facilitated and two methods of achieving this are discussed. ii Apart from this major change required in order to deal with the spectra emitted by ions of ionisation stage Z ~ 2, it is found that the radiator structure of the emitter plays an important role in the line broadening. Details of the radiator structure required for application of the LS coupling scheme, such as configuration interaction and equivalent electron configurations, are therefore taken into account where necessary. 'rhe derived theory is presented together with its properties and applied to spectral lines of a wide range of ion emitters, namely SnII, OII, OIII, SIII, SIV, AIII, AIV, NIII, NIV, ClIII, FII, CIII. The agreement obtained between theory and experiment is compared with results reported by various authors. Furthermore, attention is paid to the tre nds and regularities in Stark broadening parameters for iso-electronic and homologous ions, as well as variations with in multiplets. 'rhe presented theory is found to yield good agreement for ions of 2 4 Z < 5, compares very favourably with some other theoretical approaches in most cases, and is seen to succeed in the improvement of present calculational method